1972
DOI: 10.1126/science.178.4062.757
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Factor: Delayed Hypersensitivity to Schistosoma mansoni and Tuberculin in Macaca mulatta

Abstract: Delayed hypersensitivity in Macaca mulatta infected with either Schistosoma mansoni or mycobacteria was demonstrated by biopsies of skin test sites. Both dialyzable and nondialyzable leukocyte extracts from infected donors transferred delayed hypersensitivity to recipient monkeys. In two recipients, skin test conversion was associated with in vitro transformation of the recipients' lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…In a few instances, recipients of transfer factor have developed delayed reactivities to antigens to which the cell donors were unresponsive [53,82], and recently, a similar phenomenon has been observed in rhesus monkeys given dialyzable transfer factor from nonsensitized donors [64]. Touraine et al [103] have reported that recipients of transfer factor became responsive to chlorodinitrobenzene, an antigen to which the donors were not sensitive.…”
Section: Immunologic Properties O F Transfer Factor: the Problem O F mentioning
confidence: 88%
“…In a few instances, recipients of transfer factor have developed delayed reactivities to antigens to which the cell donors were unresponsive [53,82], and recently, a similar phenomenon has been observed in rhesus monkeys given dialyzable transfer factor from nonsensitized donors [64]. Touraine et al [103] have reported that recipients of transfer factor became responsive to chlorodinitrobenzene, an antigen to which the donors were not sensitive.…”
Section: Immunologic Properties O F Transfer Factor: the Problem O F mentioning
confidence: 88%
“…Finally, the model had to be reproducible and had to provide a quantifiable measure of CMI. Many antigens which work well in humans give poorly quantifiable results in monkeys (14). To fulfill all ofthese criteria, we chose skin sensitization to dinitrochlorobenzene (DNCB) as our model system.…”
Section: Introductionmentioning
confidence: 99%
“…Although several workers have reported successful transfers, neither the phenomenon nor the molecule are understood (1). A major problem has been the lack of easily reproduced transfers of cellular immunity by immune cell extracts in animal systems (2)(3)(4)(5).…”
mentioning
confidence: 99%